Relations among perceived stress, fatigue, and sleepiness, and their effects on the ambulatory arterial stiffness index in medical staff: A cross-sectional study - Lang, Xiaorong; Wang, Quan; Huang, Sufang; Feng, Danni; Ding, Fengfei; Wang, Wei (Frontiers in Psychology, 2022)
Objective To explore the relations among perceived stress, fatigue, sleepiness, and the pathway of their effects on the ambulatory arterial stiffness index (AASI) among medical staff. Methods This cross-sectional study was conducted at a tertiary hospital in Wuhan, China. Perceived stress, fatigue, and sleepiness were measured using the perceived stress scale (PSS), Fatigue assessment scale (FAS), and Epworth Sleepiness Scale (ESS), respectively. AASI was obtained from 24-h ambulatory blood pressure monitoring. Path analysis was used to clarify the relations among the PSS, FAS, and ESS scores, and their relations to AASI values. Results A total of 153 participants were included herein. The PSS and FAS correlated with the ESS (r = 0.424, p < 0.001), and the PSS correlated with the FAS (r = 0.614, p < 0.001). In addition, the ESS correlated with the AASI (r = 0.225, p = 0.005). According to the path analysis results, the PSS and FAS had no direct effect on the AASI, but did have an indirect effect on this index (β = 0.059, 95% confidence interval [CI] = 0.017–0.128, p = 0.005; β = 0.059, 95%CI = 0.016–0.135, p = 0.006, respectively) by influencing the ESS (β = 0.263, β = 0.262, p = 0.004). Conclusion Sleepiness was a mediator of the effects of perceived stress and fatigue on AASI.